Advances in Microwave-Assisted Production of Reduced Graphene Oxide - Xie, Xinxin; Zhou, Yanping; Huang, Kama (Frontiers in Chemistry, 2019)
Efficient reduction of graphene/graphite oxide to obtain high-quality graphene nanosheets is desirable for energy storage, catalysis, electronics and environmental remediation. In this brief review, we mainly focus on the microwave-assisted reduction of graphene/graphite oxide in two categories: (1) microwave-assisted chemical reduction of graphene oxide; (2) microwave-assisted thermal reduction of graphene oxide or simultaneous exfoliation & thermal reduction of graphite oxide. We also summarize common techniques for characterizing reduction efficiency and quality of as-obtained rGO.